The Effect of Contextual Teaching and Learning (CTL) Model towards the Student's Science Literacy on Bio Diversity in MAN 2 Banyumas - Priyani, Yahnun; Nofiana, Mufida; Julianto, Teguh (Jurnal Kiprah, 2019)
This research aimed to find out the effect of CTL model towards the student's science literacy on bio diversity inMAN 2 Banyumas. This quasi experiment research was conducted in September 2018 using posttest only controlgroup design. The samples of this research were the tenth graders of MIPA 3 as the control class and the tenth graders of MIPA 5 as the experiment class that were chosen using cluster random sampling. The data of this research were the student's science literacy score that included content, context, and science process which were collected using written test and observation. The written test was used to measure the content and context of the science literacy, while the observation was used to measure the process. The data were then analyzed using t-test, F-test, and Eta correlation test. The results showed that CTL model has a strong effect toward the student's science literacy with correlation score 0.638. CTL model also had various effects on each aspect. It showed low effect on the aspect of content with correlation score 0.296 and strong effects on the aspect of context and process with correlation score 0.644 and 0.613. Based on the results, it was concluded that CTL model had some effects toward the student's science literacy on bio diversity in MAN 2 Banyumas. Keywords: CTL Model, Student's Science Literacy, Bio Diversity